Derivation mathematical equations to estimate water surplus and groundwater recharge in Iraq - Hussein Ilaibi Zamil Al-Sudani (Applied Water Science, 2020)
Abstract Climate and hydrological conditions in any hydrological basin are multi-combined reflection of natural factors of morphology and soil nature, as well as the changing in climate factors that affect directly the hydrological cycle. The water balance equation for any natural area or water body indicates the relative values of inflow, outflow, and change in water storage for the area or water body. Estimation of water surplus and natural groundwater recharge in Iraq depending on water balance equation and meteorological data was the aim of this research. Corrected potential evapotranspiration were compared with annual and monthly rainfall in (32) meteorological stations to obtain actual evapotranspiration using water balance equation. Water surplus was divided into runoff and natural groundwater recharge where runoff coefficient method was used to estimate runoff. The obtained mathematical relationship between rainfall with both water surplus and actual evapotranspiration can be used to estimate these two parameters directly from rainfall. The results indicate that water surplus increased toward northeast direction of Iraq, while the minimum values of runoff and groundwater recharge located in western desert of Iraq. The climate conditions of desert were the major influence on reducing rainfall and rising temperature resulting decreasing water surplus, runoff, and groundwater recharge.